Investment, Organizational and Environmental Aspects of Regulation of Small and Medium Business - KRIKUNOV, Arseniy; UTEUBAYEVA, Ainur; NAZHMIDENOV, Berik; KABIEV, Ansar; SYZDYKOVA, Kulyash; BAIBASHEVA, Gulnara (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).23, 2020)
The development of small and medium-sized businesses, which is the main source of employment, attracting investments, the foundation for building a competitive economy, is one of the main priorities for the development of the national economy. In European countries, it is SMEs, within which the middle class is formed, that are the basis of stability and economic prosperity. Increased air pollution negatively affects human health and ecosystem stability. This indicator makes it possible to assess the environmental impact of certain sectors, in particular: energy, transport, industry, agriculture and waste management. In this regard, the state is trying to take measures to maintain and improve the environment through financing and tightening environmental standards.